Anti-myeloma Effects of Icariin Are Mediated Through the Attenuation of JAK/STAT3-Dependent Signaling Cascade - Jung, Young Yun; Lee, Jong Hyun; Nam, Dongwoo; Narula, Acharan S.; Namjoshi, Ojas A.; Blough, Bruce E.; Um, Jae-Young; Sethi, Gautam; Ahn, Kwang Seok (Frontiers in Pharmacology, 2018)
Because of the essential role of signal transducer and activator of transcription 3 (STAT3) in proliferation, anti-apoptosis, and chemoresistance of multiple myeloma (MM), we investigated whether icariin, a prenylated flavonol glycoside, inhibits both constitutive and inducible STAT3 activation in human myeloma cell lines. We noted that icariin could block constitutive STAT3 phosphorylation as well as its nuclear translocation and DNA binding ability in U266 cells. Icariin also suppressed IL-6-induced STAT3 activation through the inhibition of upstream kinases (Janus activated kinase-1 and -2, and c-Src). We found that icariin downregulated the protein expression of STAT3 downstream target gene products such as Bcl-2, Bcl-xl, survivin, IAP-1/2, COX-2, VEGF, and matrix metallopeptidase 9 (MMP-9) in a concentration-dependent manner. Moreover, this flavonoid also exhibited the capacity to significantly induce apoptosis and suppress proliferation of MM cells. Interestingly, this agent also significantly potentiated the apoptotic effects of bortezomib through the suppression of STAT3 activation in MM cells. Altogether, our data indicates that the potential application of icariin as a STAT3 blocker in myeloma therapy.